THE IMPORTANCE OF DIGITAL LEADERSHIP IN DIGITAL ERA - Sekar Arum; Nayla Natasya; Siti Aisyah; Muhammad Irsyad Hasibuan; Revandi Dewanta Tarigan (Universitas Efarina, 2024)
Companies in the digital age are faced with significant challenges and opportunities. These challenges include digital skills gaps, resistance to change, budget constraints and cybersecurity threats. However, the digital age also offers opportunities such as operational efficiency, business model innovation, improved customer experience and global market reach. Digital leadership is key to overcoming challenges and taking advantage of these opportunities. This research discusses strategies for implementing digital leadership values, including the development of a culture of innovation, collaboration, effective communication and data-driven decision-making. The results of the study show that the application of digital leadership values can improve company performance, encourage innovation and ensure sustainability in the digital era.